Molecular tools unveil an underestimated diversity in a stygofauna family: a preliminary world phylogeny and an updated morphology of Bathynellidae (Crustacea: Bathynellacea). Issue 1 (6th November 2017) - Camacho, Ana I; Mas-Peinado, Paloma; Dorda, Beatriz A; Casado, Adrian; Brancelj, Anton; Knight, Lee R F D; Hutchins, Benjamin; Bou, Claude; Perina, Giulia; Rey, Isabel
Abstract: Bathynella natans Vejdovsky, 1882, the first described Bathynellidae species, was found in a well in Prague. Its original description was short and incomplete, and the holotype was already damaged in 1899. The lack of type material resulted in the poor description of the type genus of the morphologically very homogeneous family. This troubled beginning is the basis of a taxonomic problem that has led to the assignment of many species in Europe and other continents to the genus Bathynella . As currently understood, the genus is cosmopolitan, with more than 50 species and subspecies, most of them insufficiently described. We analyse the systematic position of the 29 genera and approximately 100 species. This analysis includes genera from Europe, USA and Western Australia, which have been characterized with molecular data (18S and COXI ). In most cases, the genetic distances among genera and species are congruent with detected morphological differences. This is the first world molecular phylogenetic reconstruction of Bathynellidae, and it creates a framework for (1) confirming or discarding the cosmopolitan status of the genus Bathynella, (2) clarifying taxonomic uncertainties, (3) adequately describing new species, (4) advancing knowledge of the family's real diversity and (5) describing the phylogenetic relationships among genera from different continents.